Komunikasi Yang Efektif Dalam Organisasi - Rambu Nggadi May (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2015)
In an organization, all organizational activities begin with communication process. The process of goal setting, assigning tasks up to the reporting is done through communication. Communication is an action to share information, ideas and opinions of each member of the organization in order to achieve the same understanding. The sender sends a message by encoding his thoughts. In an organization, there are activities that require effective communication. For example, marketing activities will only work well if there is good communication between the marketing department and other parts such as production, finance, and other departments. Effective communication will enable the organization to achieve its goals. However, there are also organizations that fail because of poor communication. Looking at the communication process which is basically not simple, it then becomes a mandatory task of the managers or leaders in the organization to pay more attention in managing the flow of communication between members within the organization. As a medium of delivery and receiving of messages, in general communication has several functions that characterize its utilization. The functions of communication are as control, motivation, emotional expression, and information. Communication science becomes more interesting when juxtaposed with ‘intercultural’ topic. The contribution of cultural backgrounds is crucial to a person's communication behavior including understanding the perceived meanings of communication actions originating from different cultures. In order to succeed in intercultural communication, there is no other way than to study other related cultures. This will facilitate in perceiving the message in communication activities with certain parties colleagues, working partners or other parties who have different cultures.